Robert L. Fowler, The Nature of Early Greek Lyric: Three Prelimary Studies, Phoenix Supplementary Volumes Series 21, Toronto- Buffalo-London, University of Toronto Press, XII + 148 pp. ISBN 0-8020-5714-4 (Minerva, 2019)
Review: Robert L. Fowler, The Nature of Early Greek Lyric: Three Prelimary Studies, Phoenix Supplementary Volumes Series 21, Toronto- Buffalo-London, University of Toronto Press, XII + 148 pp. ISBN 0-8020-5714-4